Crack initiation, arrest and tearing assessments of a RPV subjected to PTS events. (June 2018) - Chen, Mingya; Yu, Weiwei; Qian, Guian; Shi, Jinhua; Cao, Yupeng; Yu, Yangtian
Highlights: Different types of assessments (crack initiation, arrest and tearing instability assessment) are systematically discussed. Different types of transient (with or without repressurization) are studied. The method to give the most dangerous time without the detailed fracture mechanics analysis is shown to be non-conservative. The tearing process of the RPV is still stable even for a big initial crack according to the newly results. Abstract: Although the resistance of reactor pressure vessel (RPV) against fast fracture has to be proven by comprehensive analyses, there are few published literatures systematically discussing the crack initiation, arrest and tearing instability assessment in the pressurized thermal shock (PTS) events. In this paper, three types of assessment are discussed and studied. For the rapid cool-down of the typical PTS transients, the temperature of the deepest point along the crack tip is often high enough to ensure that both crack arrest assessment and crack tearing instability assessment can be used to prevent the RPV failure after the crack initiation occurs. When the assessment is changed from the crack initiation assessment to the crack arrest assessment, the transition temperature region of the material toughness curve moves towards to the right which leads to an increase of the area in which the brittle cleavage fracture may occur. It is not possible to determine the most dangerous moment before the detailed analysis of fracture mechanism. So the method of assessment the most dangerous moment which is given in the initial input data may be non-conservative. As the conservative crack shape parameter and method to consider the plastic correction are used in the French RCC-M code, the size of critical crack is very small in the case study. While according to the new study results, the tearing process of the RPV is still stable even for a big initial crack which is larger than the maximum hypothetical crack size in the code.